2D organic–inorganic nanosheets via self-assembly of a pillar[6]arene and polyoxometalate for enhanced degradation efficiency. Issue 49 (31st May 2018) - Cheng, Ni; Chen, Yong; Wu, Xuan; Liu, Yu
Abstract : Pillar[6]arene induced the aggregation of 2D nanosheets and enhanced the degradation efficiency of the polyoxometalate. Abstract : Construction of 2D hybrid nanosheets was realized through a self-assembly strategy using a pillar[6]arene (P6 ) and polyoxometalate (POM) in water. More fascinatingly, the macrocyclic cavity of P6 could impose a restriction effect on the lamellar arrangement and significantly enhance the catalytic ability of nanosheets for dye degradation.